The Effect of Perceived Value, Service Quality, Trust, and Passenger Satisfaction on Passenger Loyalty of Ferry Batam Jet at PT Pelayaran Batam Bahari Sejahtera - Eky Pratiwi; Andika Prasetya Nugraha; Netti Syafitri (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
Passenger loyalty is a critical factor in the sustainability of transportation service companies, particularly in ferry services where passengers have various alternative modes of transport. This study aims to analyze the effect of perceived value, service quality, trust, and passenger satisfaction on passenger loyalty of Ferry Batam Jet at PT Pelayaran Batam Bahari Sejahtera. A quantitative explanatory research design was employed to examine the causal relationships among the variables. Data were collected through structured questionnaires distributed to passengers who had used the Ferry Batam Jet service. The population of this study consisted of Ferry Batam Jet passengers, with a sample of 100 respondents selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, the data were examined through validity and reliability tests as well as classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, to ensure the feasibility of the regression model. The results indicate that perceived value has a positive and significant effect on passenger loyalty. Service quality is also found to significantly influence passenger loyalty, demonstrating that reliable and responsive service delivery strengthens repeat usage intentions. Trust shows a significant and positive effect and emerges as the most dominant variable influencing loyalty, highlighting the importance of credibility and reliability in ferry transportation services. Passenger satisfaction also has a significant effect on loyalty, confirming that positive overall travel experiences encourage passengers to reuse and recommend the service. Simultaneously, perceived value, service quality, trust, and passenger satisfaction have a significant effect on passenger loyalty. These findings suggest that passenger loyalty in ferry transportation is formed through an integrated evaluation of value, service performance, trust, and satisfaction. This study provides practical implications for ferry operators to enhance loyalty by improving service quality, strengthening trust, managing passenger expectations, and ensuring consistent satisfaction. The study contributes empirical evidence to the literature on service marketing and transportation management, particularly in the context of ferry transportation services.